MANAJEMEN TEKNIS PRODUKSI PETERNAKAN PUYUH (STUDI KASUS DI PETERNAKAN MASAGENA KECAMATAN TENAYAN RAYA) - Melli Wahyuri; Elfi Rahmadani; Elfawati Elfawati (Jurnal Peternakan, 2014)
The purpose of this study was to describe the development of business as well as to analyze the aspects of production and determine the feasibility of breeding quail in Livestock Masagena from 2006 to 2010. The study was conducted from May to June 2011. The data consisted of primary and secondary data. Primary data were hatchability, mortality, hen day egg production, meat production, by product, the characteristic of the respondents, marketing, technical maintenance, financial analysis, fixed costs and variable costs. Secondary data was the data from the Village Office and Head Office. Case study research method was determined by purposive sampling. Data collected by observation and interviews directly with respondents using questionnaires. Data of quail production were analyzed using mean and standard deviation, while for financial feasibility quantitatively was analyzed descriptively. The results showed that the average production Ranch quail egg hatchability Masagena coverr were 78.59%, 3.09% mortality quail, hen day egg production and meat production 62.24%, 152.51 head/day. Financial feasibility analysis results showed a positive NPV, BCR was more than one, and the IRR was higher than the interest rate, indicated that the Ranch Masagena financially viable to run.